Flood Control in Areas of Cisumdawu Toll Road Section 3 at Galudra Village, Sumedang Regency. - Fada, Arsyadin Abil; Setiawan, David; Tisna, Muhamad; Abdurahman, Piki; Siddiq, R.H.B Ash (International Journal of Psychosocial Rehabilitation, 2020)
Flooding is a problem that often occurs in urban and rural areas. Flooding can be caused by an overflow of drainage flow that exceeds its capacity. In 2019, Galudra Village, Sumedang Utara Subdistrict flooding happened, the cause of the flood was indicated since the Cisumdawu development project, based on observations in fields, the flood caused by the overflow of local drainage flows that caused inundation of 20-50 cm which inundated the paddy field and Galudra Village area. From the results of the hydrological analysis, it was found that the Catchment Area at the study site was divided into 2, with each area of   Subcatchment 1 being 283.1 ha and the area of   sub-catchment 2 being 414.9 ha. With extreme rain period of 2 years (R2) of 91.05 mm and an extreme rain period of 5 years (R5) is 107.59 mm. From the results of SWMM modeling, it is found that the most effective flood control is by bypassing the channel and enlarging the downstream channel dimensions in the form of a trapezoid.